2020
DOI: 10.26464/epp2020035
|View full text |Cite
|
Sign up to set email alerts
|

Response of photoelectron peaks in the Martian ionosphere to solar EUV/X-ray irradiance

Abstract: The photoelectron peaks near 27 eV and 500 eV are investigated, related to HeII 30.4 nm ionization and O Auger ionization q The 500 eV peak intensity increases with increasing solar irradiance much more rapidly than the 27 eV peak intensity q The observation is consistent with a larger variability in solar radiance at shorter wavelengths

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The above spectral features have been extensively observed over the past four decades (e.g. Frahm et al., 2006b; Mantas & Hanson, 1979; Peterson et al., 2016; Sakai et al., 2015; Wu et al., 2020a).…”
Section: Introductionmentioning
confidence: 90%
“…The above spectral features have been extensively observed over the past four decades (e.g. Frahm et al., 2006b; Mantas & Hanson, 1979; Peterson et al., 2016; Sakai et al., 2015; Wu et al., 2020a).…”
Section: Introductionmentioning
confidence: 90%
“…Indeed, the energy range below 50 eV encompasses the strong He II peak whereas the range of 500-800 eV encompasses the Auger peak driven by the prominent process of inner shell ionization of atmospheric CO 2 and O (X. Wu et al, 2020).…”
Section: Comparisons Between Different Model Runsmentioning
confidence: 99%
“…In addition to the cold plasma, the Martian ionosphere contains hot plasma, with photoelectrons making up an important component also produced by atmospheric photoionization (Coates et al., 2011). Similar to cold electrons, the characteristics of photoelectrons such as the intensity and spectral shape have been observed to be systematically correlated with the solar EUV and SXR irradiance (Cheng et al., 2022; Gramapurohit et al., 2021; X. Wu et al., 2020; X. S. Wu et al., 2019). A typical photoelectron energy spectrum is characterized by several pronounced features including the He II peak at 22–27 eV, the Auger peak at 300–500 eV, along with the aluminum edge at 60–70 eV, all acknowledged signatures of the interaction of solar photons with atmospheric neutrals (Peterson et al., 2016; Sakai et al., 2015).…”
Section: Motivationmentioning
confidence: 99%
“…For instance, Wu, Cui, Cao et al. (2020) showed that both the He II and Auger peak intensities increased steadily with increasing solar ionizing flux, with the solar response of the latter being more intense than the former owing to the wavelength‐dependent variation of the solar flux during a solar cycle (e.g., Peterson et al., 2016). In addition, the photoelectron intensity above the photoelectron exobase (the location where the photoelectrons become collisionless) shows essentially no or weak correlation with the solar zenith angle (SZA) (Xu, Liemohn, et al., 2016), presumably linked to the optically thin nature of the Martian atmosphere at these altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, they could also be used to infer the strength of the ambipolar electric field (Collinson et al., 2017, 2019; Xu et al., 2018), which is crucial for evaluating plasma escape on Mars (Ma et al., 2019). Existing observations of the Martian photoelectron energy distribution have revealed complicated variations with the incident solar irradiance (e.g., Gramapurohit et al., 2021; Wu, Cui, Cao, et al., 2020; Xu, Liemohn, et al., 2016) and atmospheric structure and composition (Wu, Cui, Yelle, et al., 2020; Xu et al., 2014, 2015). For instance, Wu, Cui, Cao et al.…”
Section: Introductionmentioning
confidence: 99%